Bahasa Hukum Dalam Perspektif Rasionalisme - Wiwik Harjanti (Fakultas Hukum Universitas Mulawarman, 2010)
Rasionalism has an important role in the Indonesian law system which is tend to be positivistic. Legal terminology linking the result of penal circumstantial ratio which arrange human life in order to reach prosperity of society of the state. In this case, rasionalism order that the law terminology has to be excepted by it is logic racionality so that can be understand, to be comprehended and executed by the citizen.